Catalyst, electrode catalyst layer, membrane electrode assembly and fuel cell using the same
By using a catalyst with a specific hole distribution in the fuel cell, the problems of high usage amount and insufficient catalytic activity of noble metal catalysts are solved, and more efficient gas delivery and stable catalytic performance are achieved, reducing the cost of the fuel cell.
Patent Information
- Application Number
- CN202110189933.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2013-04-25
- Filing Date
- 2014-04-14
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2034-04-14
AI Technical Summary
The high amount of precious metal catalysts used in existing fuel cells leads to high cost of fuel cells and insufficient catalytic activity and gas transportability, especially under high load conditions.
A catalyst with a specific hole distribution is used. The catalyst consists of a catalyst support and a metal catalyst supported on the support. There are tiny pores with a radius less than 1 nm and fine pores with a radius more than 1 nm. The metal catalyst is supported in the fine pores. Ensure gas delivery path and catalytic activity.
The catalytic activity and gas transportability of the catalyst are improved, the use of precious metal catalysts is reduced, the production cost of fuel cells is reduced, and the performance is more stable under high load conditions.
Smart Images

Figure CN112993270B_ABST
Abstract
Description
[0001] This application is a divisional application of a Chinese invention patent application filed on April 14, 2014, with application number 201480022907.6, and the invention name is "Catalyst and electrode catalyst layer, membrane electrode assembly and fuel cell using the same", and the applicant is Nissan Motor Co., Ltd. Technical Field
[0002] The present invention relates to a catalyst, in particular, an electrode catalyst used in a fuel cell (PEFC), and an electrode catalyst layer, a membrane electrode assembly and a fuel cell using the catalyst. Background Art
[0003] Solid polymer fuel cells using proton conductive solid polymer membranes operate at lower temperatures than other types of fuel cells such as solid oxide fuel cells and molten carbonate fuel cells. Therefore, solid polymer fuel cells are expected to be used as stationary power sources or power sources for mobile bodies such as automobiles, and their practical application is also beginning.
[0004] Such solid polymer fuel cells generally use expensive metal catalysts represented by Pt (platinum) or Pt alloys, which is the main reason for the high price of such fuel cells. Therefore, it is required to develop a technology that can reduce the amount of precious metal catalysts used and achieve low cost of fuel cells.
[0005] For example, Patent Document 1 discloses an electrode catalyst in which metal catalyst particles are supported on a conductive carrier, wherein the average particle size of the metal catalyst particles is larger than the average pore size of the micropores of the conductive carrier. Patent Document 1 records that, by this structure, the metal catalyst particles cannot enter the micropores of the carrier, and the proportion of the metal catalyst particles used at the three-phase interface can be increased, thereby improving the utilization efficiency of the expensive precious metal.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: (Japanese) Patent Application Publication No. 2007-250274 (US Patent Application Publication No. 2009 / 0047559)
[0009] However, the catalyst of Patent Document 1 has the problem that the electrolyte and the metal catalyst particles are in contact, and the catalytic activity is reduced. On the other hand, when the metal catalyst is supported in fine cavities in the carrier where the electrolyte cannot enter in a manner that the electrolyte and the metal catalyst particles are not in contact, the transport distance of gases such as oxygen will increase, and the gas transportability will decrease, so there are the following problems: the catalytic activity is not fully manifested, and the catalyst performance is reduced under high load conditions. Summary of the invention
[0010] Therefore, the present invention has been made in view of the above circumstances, and an object of the present invention is to provide a catalyst having excellent catalytic activity and gas transport properties.
[0011] Another object of the present invention is to provide an electrode catalyst layer, a membrane electrode assembly, and a fuel cell having excellent power generation performance.
[0012] The present inventors have conducted intensive studies to solve the above problems. As a result of the studies, they have found that a catalyst having a specific hole distribution can solve the above problems, and have completed the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is a schematic cross-sectional view showing the basic structure of a solid polymer fuel cell according to one embodiment of the present invention;
[0014] Figure 2 This is a schematic cross-sectional explanatory diagram showing the shape and structure of a catalyst according to one embodiment of the present invention;
[0015] Figure 3 is a schematic diagram showing the relationship between a catalyst and an electrolyte in a catalyst layer according to one embodiment of the present invention;
[0016] Figure 4 This is a diagram showing the hole distribution of Comparative Catalysts F to H of Comparative Examples 1 to 3.
[0017] Explanation of symbols
[0018] 1 Polymer electrolyte fuel cell (PEFC)
[0019] 2 Solid polymer electrolyte membrane
[0020] 3 Catalyst layer
[0021] 3a Anode catalyst layer
[0022] 3c Cathode catalyst layer
[0023] 4a Anode gas diffusion layer
[0024] 4c Cathode gas diffusion layer
[0025] 5. Partition
[0026] 5a Anode separator
[0027] 5c Cathode separator
[0028] 6a Anode gas flow path
[0029] 6c Cathode gas flow path
[0030] 7 Refrigerant flow path
[0031] 10 Membrane Electrode Assembly (MEA)
[0032] 20 Catalyst
[0033] 22 Metal Catalyst
[0034] 23 Carrier
[0035] 24 tiny holes
[0036] 25 micro holes
[0037] 26 Electrolytes DETAILED DESCRIPTION
[0038] The catalyst of the present invention (also referred to as "electrode catalyst" in this specification) is composed of a catalyst carrier and a metal catalyst supported on the catalyst carrier. Here, the catalyst satisfies the following structures (a) to (c):
[0039] (a) The catalyst has holes (primary holes) with a radius of less than 1 nm and holes (primary holes) with a radius of more than 1 nm;
[0040] (b) the hole volume of the holes with a radius of less than 1 nm is 0.3 cc / g carrier or more; and
[0041] (c) The metal catalyst is supported inside the cavity having a radius of 1 nm or more.
[0042] Furthermore, the catalyst of the present invention is composed of a catalyst carrier and a metal catalyst supported on the catalyst carrier.
[0043] Here, the catalyst satisfies the following structures (a), (d) and (c):
[0044] (a) The catalyst has holes with a radius of less than 1 nm and holes with a radius of more than 1 nm;
[0045] (d) the model radius of the hole distribution of the holes having a radius of less than 1 nm is 0.3 nm or more and less than 1 nm; and
[0046] (c) The metal catalyst is supported inside the cavity having a radius of 1 nm or more.
[0047] According to the catalyst having the above structure, since the metal catalyst is contained in a relatively large hole to suppress contact with the electrolyte, and the gas transport path is ensured by a relatively small hole, the gas transport performance can be improved. And, as a result, a catalyst with excellent catalytic activity can be provided. In addition, in this specification, a hole with a radius of less than 1nm is also referred to as a "micro hole". In addition, in this specification, a hole with a radius of more than 1nm is also referred to as a "meso hole".
[0048] The inventors have found that in the catalyst described in the above-mentioned patent document 1, because the electrolyte (electrolyte polymer) is easier to adsorb on the catalyst surface than gases such as oxygen, when the metal catalyst contacts the electrolyte (electrolyte polymer), the reactive area of the catalyst surface is reduced. In contrast, the inventors have found that even when the catalyst is not in contact with the electrolyte, the catalyst can be effectively utilized by forming a three-phase interface by water. Therefore, by taking the structure in which the above-mentioned (c) metal catalyst is supported on the inside of the fine pores that the electrolyte cannot enter, the catalytic activity can be improved.
[0049] On the other hand, when the metal catalyst is carried inside the fine pores that the electrolyte cannot enter, the transport distance of gases such as oxygen increases, and the gas transport property decreases, so it will not reflect sufficient catalytic activity, and under high load conditions, the catalyst performance will decrease. In contrast, by fully ensuring the hole volume of the micropores that most or all of the above-mentioned (b) electrolytes or metal catalysts cannot enter, or setting the model diameter of the above-mentioned (d) micropores to a larger degree, the gas transport path can be fully ensured. Therefore, it is possible to efficiently transport gases such as oxygen to the metal catalyst in the fine pores, that is, it is possible to reduce gas transport resistance. Through this structure, gas (for example, oxygen) can pass through the micropores (gas transportability is improved), and the gas can be efficiently contacted with the catalyst.
[0050] Therefore, according to the present invention, since the micropores exist in a large volume, the reaction gas can be transported to the surface of the metal catalyst present in the micropores through the micropores (paths), so the gas transport resistance is small. Therefore, the catalyst of the present invention can exert high catalytic activity, that is, it can promote the catalytic reaction. Therefore, the membrane electrode assembly and the fuel cell having the catalyst layer using the catalyst of the present invention have excellent power generation performance.
[0051] Below, an embodiment of the catalyst of the present invention, as well as an embodiment of a catalyst layer, a membrane electrode assembly (MEA), and a fuel cell using the catalyst are described in detail with appropriate reference to the accompanying drawings. However, the present invention is not limited to the following embodiments. In addition, the drawings are exaggerated for ease of description, and the dimensional ratios of the components of the drawings are sometimes different from the actual ones. In addition, when the embodiments of the present invention are described with reference to the accompanying drawings, the same symbols are attached to the same components in the description of the drawings, and repeated descriptions are omitted.
[0052] In addition, in this specification, "X to Y" indicating a range means "more than X and less than Y", and "weight" and "mass", "weight %" and "mass %", and "weight parts" and "mass parts" are treated as synonyms. In addition, unless otherwise specified, the operation and measurement of physical properties are measured under the conditions of room temperature (20 to 25°C) / relative humidity 40 to 50%.
[0053] [Fuel Cell]
[0054] The fuel cell has a membrane electrode assembly (MEA) and a pair of separators, the pair of separators being composed of an anode side separator having a fuel gas flow path for the flow of fuel gas, and a cathode side separator having an oxidant gas flow path for the flow of oxidant gas. The fuel cell of this mode has excellent durability and can exhibit high power generation performance.
[0055] Figure 1 This is a schematic diagram showing the basic structure of a solid polymer fuel cell (PEFC) 1 according to one embodiment of the present invention. First, the PEFC 1 has a solid polymer electrolyte membrane 2 and a pair of catalyst layers (anode catalyst layer 3a and cathode catalyst layer 3c) sandwiching the solid polymer electrolyte membrane 2. In addition, the stack of the solid polymer electrolyte membrane 2 and the catalyst layers (3a, 3c) is further sandwiched by a pair of gas diffusion layers (GDL) (anode gas diffusion layer 4a and cathode gas diffusion layer 4c). In this way, the solid polymer electrolyte membrane 2, the pair of catalyst layers (3a, 3c) and the pair of gas diffusion layers (4a, 4c) are stacked together to form a membrane electrode assembly (MEA) 10.
[0056] In PEFC 1, MEA 10 is further sandwiched by a pair of separators (anode separator 5a and cathode separator 5c). Figure 1In the figure, the separators (5a, 5c) are shown as being located at both ends of the MEA 10 shown in the figure. In a fuel cell stack formed by stacking a plurality of MEAs, the separators are usually also used as separators for adjacent PEFCs (not shown). In other words, in a fuel cell stack, MEAs are stacked in sequence via separators to form a cell stack. In addition, in an actual fuel cell stack, a gas sealing portion is provided between the separators (5a, 5c) and the solid polymer electrolyte membrane 2, or between the PEFC 1 and another adjacent PEFC, but in Figure 1 Their records are omitted.
[0057] The partitions (5a, 5c) are formed into the following shapes by, for example, pressing a thin plate having a thickness of 0.5 mm or less. Figure 1 The convex and concave shape shown in the figure is obtained. The convex part of the separator (5a, 5c) seen from the MEA side is in contact with the MEA10. Thus, the electrical connection with the MEA10 is ensured. In addition, the concave part of the separator (5a, 5c) seen from the MEA side (the space between the separator and the MEA generated by the concave and convex shape of the separator) functions as a gas flow path for gas circulation during the operation of the PEFC1. Specifically, the fuel gas (for example, hydrogen, etc.) is circulated in the gas flow path 6a of the anode separator 5a, and the oxidant gas (for example, air, etc.) is circulated in the gas flow path 6c of the cathode separator 5c.
[0058] On the other hand, the recessed portion of the separator (5a, 5c) viewed from the side opposite to the MEA side is provided as a refrigerant flow path 7 for circulating a refrigerant (e.g., water) for cooling the PEFC during operation of the PEFC 1. Furthermore, a manifold (not shown) is generally provided on the separator. The manifold functions as a connecting device for connecting each single cell when forming a battery stack. By adopting such a structure, the mechanical strength of the fuel cell stack can be ensured.
[0059] In addition, Figure 1 In the embodiment shown, the partitions (5a, 5c) are formed into a concave-convex shape. However, the partitions are not limited to such a concave-convex shape, and can be in any shape such as a flat plate shape or a partially concave-convex shape as long as they can function as a gas flow path and a refrigerant flow path.
[0060] The fuel cell with MEA of the present invention as described above exerts excellent power generation performance. Here, as the type of fuel cell, it is not particularly limited. In the above description, polymer electrolyte fuel cells are used as an example for description, but in addition, alkaline fuel cells, direct methanol fuel cells, micro fuel cells, etc. can also be cited. Among them, from the perspective of small size and high density and high output, polymer electrolyte fuel cells (PEFC) are preferably cited. In addition, in addition to being used as a mobile power source for vehicles with limited carrying space, the above-mentioned fuel cell is also used as a fixed power source, etc. Among them, it is particularly preferably used as a mobile power source for automobiles, etc. that request high output voltage after a relatively long period of operation stop.
[0061] The fuel used to operate the fuel cell is not particularly limited. For example, hydrogen, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, sec-butanol, tert-butanol, dimethyl ether, diethyl ether, ethylene glycol, diethylene glycol, etc. can be used. Among them, hydrogen or methanol is preferably used in terms of achieving high output.
[0062] In addition, the application of the fuel cell is not particularly limited, but it is preferably applied to vehicles. The electrolyte membrane-electrode assembly of the present invention is excellent in power generation performance and durability, and can be miniaturized. Therefore, from the perspective of vehicle-mountability, the fuel cell of the present invention is particularly advantageous when the fuel cell is applied to a vehicle.
[0063] Hereinafter, components constituting the fuel cell of this embodiment will be briefly described, but the technical scope of the present invention is not limited to the embodiment described below.
[0064] [Catalyst (electrode catalyst)]
[0065] Figure 2 1 is a schematic cross-sectional view showing the shape and structure of a catalyst according to one embodiment of the present invention. Figure 2As shown, the catalyst 20 of the present invention is composed of a metal catalyst 22 and a catalyst carrier 23. In addition, the catalyst 20 has a hole (micropore) 25 with a radius of less than 1 nm and a hole (fine pore) 24 with a radius of more than 1 nm. Here, the metal catalyst 22 is carried inside the fine pore 24. In addition, as long as at least a part of the metal catalyst 22 is carried inside the fine pore 24, a part of it can also be carried on the surface of the catalyst carrier 23. However, from the viewpoint of preventing the contact between the electrolyte and the metal catalyst of the catalyst layer, it is preferred that substantially all of the metal catalyst 22 is carried inside the fine pore 24. Here, "substantially all of the metal catalyst" is not particularly limited as long as it is an amount that can improve the catalytic activity sufficiently. "Substantially all of the metal catalyst" is preferably present in an amount of 50% by weight or more (upper limit: 100% by weight) in the total metal catalyst, and more preferably in an amount of 80% by weight or more (upper limit: 100% by weight).
[0066] In this specification, "the metal catalyst is supported inside the fine pores" can be confirmed by the reduction in the volume of the fine pores before and after the metal catalyst is supported on the catalyst carrier. In detail, the catalyst carrier (hereinafter, also referred to as "carrier") has micropores and fine pores, and each hole has a certain volume, but when the metal catalyst is supported on these holes, the volume of each hole will decrease. Therefore, when the difference between the volume of the fine pores of the catalyst (carrier) before the metal catalyst is supported and the volume of the fine pores of the catalyst (carrier) after the metal catalyst is supported [=(volume before support) - (volume after support)] exceeds 0, it becomes a situation of "the metal catalyst is supported inside the fine pores". Similarly, when the difference between the volume of the fine pores of the catalyst (carrier) before the metal catalyst is supported and the volume of the fine pores of the catalyst (carrier) after the metal catalyst is supported [=(volume before support) - (volume after support)] exceeds 0, it becomes a situation of "the metal catalyst is supported inside the fine pores". It is preferred that the metal catalyst is mostly loaded in the fine pores compared to the micropores (i.e., the reduction in the volume of the fine pores before and after loading is greater than the reduction in the volume of the micropores before and after loading). This can reduce the gas transport resistance and fully ensure the path for gas transport. When considering the reduction in gas transport resistance, the ensuring of the path for gas transport, etc., the reduction in the hole volume of the fine pores before and after the metal catalyst is loaded is preferably 0.02cc / g or more, more preferably 0.02 to 0.4cc / g.
[0067] In addition, the hole volume of the hole (micropore) with a radius less than 1nm (of the catalyst after the metal catalyst is supported) is more than 0.3cc / g carrier and / or the model radius (maximum frequency diameter) of the hole distribution of the micropore (of the catalyst after the metal catalyst is supported) is more than 0.3nm and less than 1nm. Preferably, the hole volume of the micropore is more than 0.3cc / g carrier, and the model radius of the hole distribution of the micropore is more than 0.3nm and less than 1nm. If the hole volume and / or model diameter of the micropore are within the range as described above, sufficient micropores can be ensured for gas transport, and the gas transport resistance is small. Therefore, a sufficient amount of gas can be transported to the surface of the metal catalyst present in the fine pores via the micropore (path), so the catalyst of the present invention can exert high catalytic activity, that is, it can promote catalytic reaction. In addition, in the micropore, the electrolyte (ionomer) or liquid (for example, water) cannot invade, and only the gas is selectively passed through (the gas transport resistance can be reduced). When considering the effect of improving gas transportability, the hole volume of the micropores is more preferably 0.3 to 2 cc / g of carrier, and particularly preferably 0.4 to 1.5 cc / g of carrier. In addition, the model radius of the hole distribution of the micropores is more preferably 0.4 to 1 nm, and particularly preferably 0.4 to 0.8 nm. In addition, in this specification, the hole volume of holes with a radius of less than 1 nm is also referred to as "hole volume of micropores." Similarly, in this specification, the model radius of the hole distribution of micropores is also referred to as "model diameter of micropores."
[0068] The hole volume of holes (fine pores) with a radius of more than 1 nm (of the catalyst after the metal catalyst is supported) is not particularly limited, but is preferably more than 0.4cc / g of the carrier, more preferably 0.4-3cc / g of the carrier, and particularly preferably 0.4-1.5cc / g of the carrier. If the hole volume is within the range as described above, more metal catalysts can be stored (loaded) in the fine pores, so that the electrolyte and the metal catalyst of the catalyst layer are physically separated (the contact between the metal catalyst and the electrolyte can be more effectively suppressed and prevented). Therefore, the activity of the metal catalyst can be more effectively utilized. In addition, by utilizing the presence of many fine pores, the role and effect of the present invention can be more significantly exerted, thereby more effectively promoting the catalytic reaction. In addition, the micropores act as a gas transport path, and the three-phase interface is more significantly formed by water, thereby further improving the catalytic activity. In addition, in this specification, the hole volume of holes with a radius of more than 1 nm is also referred to as "hole volume of fine pores".
[0069] The model radius (maximum frequency diameter) of the hole distribution of holes (fine pores) with a radius of more than 1 nm (of the catalyst after the metal catalyst is loaded) is not particularly limited, but is preferably 1 to 5 nm, more preferably 1 to 4 nm, and particularly preferably 1 to 3 nm. If it is the model diameter of the hole distribution of the fine pores as described above, a sufficient amount of metal catalyst can be stored (loaded) by the fine pores, so that the electrolyte and the metal catalyst of the catalyst layer are physically separated (the contact between the metal catalyst and the electrolyte can be more effectively suppressed and prevented). Therefore, the activity of the metal catalyst can be more effectively utilized. In addition, by utilizing the presence of large-volume fine pores, the role and effect of the present invention can be more significantly exerted, and the catalytic reaction can be more effectively promoted. In addition, the micropores act as a gas transport path, and the catalytic activity can be further improved by the more significant three-phase interface of water. In addition, in this specification, the model radius of the hole distribution of the fine pores is also referred to as the "model diameter of the fine pores".
[0070] BET specific surface area (of the catalyst after metal catalyst support) [BET specific surface area of the catalyst per 1 g of the support (m 2 / g carrier)] is not particularly limited, but is preferably 1000m 2 / g carrier or more, more preferably 1000 to 3000 m 2 / g carrier, particularly preferably 1100 to 1800 m 2 / g carrier. If it is the specific surface area as described above, sufficient fine pores and micropores can be ensured, so it is possible to ensure sufficient micropores (lower gas transport resistance) for gas transport, and more metal catalysts can be stored (loaded) by the fine pores. In addition, the electrolyte and the metal catalyst of the catalyst layer are physically separated (the contact between the metal catalyst and the electrolyte can be more effectively suppressed and prevented). Therefore, the activity of the metal catalyst can be more effectively utilized. In addition, by utilizing the presence of many micropores and fine pores, the effect and effect of the present invention can be more significantly exerted, and the catalytic reaction can be more effectively promoted. In addition, the micropores play a role as a gas transport path, and the three-phase interface is more significantly formed by water, which can further improve the catalytic activity.
[0071] In addition, in this specification, the "BET specific surface area (m 2 / g carrier)" is measured by nitrogen adsorption method. In detail, about 0.04-0.07g of catalyst powder is accurately weighed and sealed in a test tube. The test tube is pre-dried at 90°C for several hours in a vacuum dryer as a sample for measurement. For weighing, an electronic balance (AW220) manufactured by Shimadzu Corporation is used. In addition, in the case of a coated sheet, the net weight of the coating layer obtained by subtracting the weight of Teflon (registered trademark) (substrate) of the same area from the total weight of the coated sheet is about 0.03-0.04g as the sample weight. Then, the BET specific surface area is measured under the following measurement conditions. A BET curve is prepared on the adsorption side of the adsorption and desorption isotherms according to the relative pressure (P / P0) range of about 0.00-0.45, and the BET specific surface area is calculated based on its slope and slice.
[0072] [Chemistry 1]
[0073] <Measurement conditions>
[0074] Measuring device: High-precision fully automatic gas adsorption device BELSORP36 manufactured by Japan Bell Co., Ltd.
[0075] Adsorption gas: N2
[0076] Dead volume measurement gas: He
[0077] Adsorption temperature: 77K (liquid nitrogen temperature)
[0078] Pre-measurement treatment: 90℃ vacuum drying for several hours (after removing He, place on the measurement workbench)
[0079] Measurement mode: isothermal adsorption and desorption process
[0080] Measuring relative pressure (P / P0): about 0~0.99
[0081] Balance setting time: 180 seconds per 1 relative pressure
[0082] "The radius of the hole of the micropore (nm)" refers to the radius of the hole measured by the nitrogen adsorption method (MP method). In addition, the "model radius of the hole distribution of the micropore (nm)" refers to the hole radius of the point with a peak value (maximum frequency) in the differential pore distribution curve obtained by the nitrogen adsorption method (MP method). Here, the lower limit of the hole radius of the micropore is the lower limit value that can be measured by the nitrogen adsorption method, that is, above 0.42nm. Similarly, the "radius of the hole of the fine pore (nm)" refers to the radius of the hole measured by the nitrogen adsorption method (DH method). In addition, the "model radius of the hole distribution of the fine pore (nm)" refers to the hole radius of the point with a peak value (maximum frequency) in the differential pore distribution curve obtained by the nitrogen adsorption method (DH method). Here, the upper limit of the hole radius of the fine pore is not particularly limited, but is below 5nm.
[0083] "The hole volume of micropores" refers to the total volume of micropores with a radius of less than 1 nm present in the catalyst, expressed as the volume per 1g of carrier (cc / g carrier). "The hole volume of micropores (cc / g carrier)" is calculated as the area (integral value) of the lower part of the differential pore distribution curve obtained by the nitrogen adsorption method (MP method). Similarly, "the hole volume of fine pores" refers to the total volume of fine pores with a radius of more than 1 nm present in the catalyst, expressed as the volume per 1g of carrier (cc / g carrier). "The hole volume of fine pores (cc / g carrier)" is calculated as the area (integral value) of the lower part of the differential pore distribution curve obtained by the nitrogen adsorption method (DH method).
[0084] "Differential pore distribution" is a distribution curve drawn with the pore diameter as the horizontal axis and the pore volume in the catalyst equivalent to the pore diameter as the vertical axis. That is, when the hole volume of the catalyst obtained by the nitrogen adsorption method (MP method in the case of micropores; DH method in the case of small pores) is V and the hole diameter is D, the value (dV / d(logD)) obtained by dividing the differential hole volume dV by the logarithmic difference d(logD) of the hole diameter is obtained. Then, by plotting this dV / d(logD) against the average hole diameter of each type, the differential pore distribution curve is obtained. The differential hole volume dV refers to the increase in hole volume between measurement points.
[0085] Here, the method for measuring the radius and the void volume of the micropores by the nitrogen adsorption method (MP method) is not particularly limited, and for example, the method described in the known literature such as "Science of Adsorption" (2nd edition, co-authored by Seiichi Kondo, Tatsuo Ishikawa, and Ikuo Abe, Maruzen Co., Ltd.), "Analysis Methods of Fuel Cells" (edited by Yoshio Takasu, Masaru Yoshitake, and Tatsuki Ishihara, Chemical Dojin), R. Sh. Mikhail, S. Brunauer, EEBodor J. Colloid Interface Sci., 26, 45 (1968) can be used. In this specification, the radius and the void volume of the micropores measured by the nitrogen adsorption method (MP method) are the values measured by the method described in R. Sh. Mikhail, S. Brunauer, EEBodor J. Colloid Interface Sci., 26, 45 (1968).
[0086] In addition, the method for measuring the radius and the pore volume of the fine pore by the nitrogen adsorption method (DH method) is not particularly limited, and for example, the method described in the known literature such as "Science of Adsorption" (2nd edition, co-authored by Seiichi Kondo, Tatsuo Ishikawa, and Ikuo Abe, Maruzen Co., Ltd.) or "Analysis Methods of Fuel Cells" (edited by Yoshio Takasu, Masaru Yoshitake, and Tatsuki Ishihara, Chemical Dojin), D. Dollion, GR Heal: J. Appl. Chem., 14, 109 (1964) can be used. In this specification, the radius and the pore volume measured by the nitrogen adsorption method (DH method) are the values measured by the method described in D. Dollion, GR Heal: J. Appl. Chem., 14, 109 (1964).
[0087] The manufacturing method of the catalyst with specific hole distribution as described above is not particularly limited, but it is usually important to set the hole distribution (micropores and fine holes) of the carrier to the hole distribution as described above. Specifically, as a method for manufacturing a carrier with micropores and fine holes, and the hole volume of the micropores is more than 0.3cc / g carrier, preferably using (Japan) Patent Publication No. 2010-208887 (U.S. Patent Application Publication No. 2011 / 318254 Specification, hereinafter the same,) or International Publication No. 2009 / 75264 (U.S. Patent Application Publication No. 2011 / 058308 Specification, hereinafter the same,) and other publications described in the method. In addition, as a method for manufacturing a carrier with micropores and fine holes, and the model radius of the hole distribution of the micropores is more than 0.3nm and less than 1nm, preferably using (Japan) Patent Publication No. 2010-208887 or International Publication No. 2009 / 75264 and other publications described in the method.
[0088] The material of the carrier is not particularly limited as long as it is a material that can form holes (primary holes) having the above-mentioned hole volume or model diameter inside the carrier, and has a sufficient specific surface area and sufficient electronic conductivity to support the catalyst components in a dispersed state inside the fine pores. The preferred main component is carbon. Specifically, carbon particles composed of carbon black (ketjen black, oil furnace black, channel black, lampblack, thermal black, acetylene black, etc.), activated carbon, etc. can be cited. "The main component is carbon" means that it contains carbon atoms as the main component, which is a concept that includes both being composed of only carbon atoms and being substantially composed of carbon atoms, and may also contain elements other than carbon atoms. "Substantially composed of carbon atoms" means that impurities of less than 2 to 3% by weight can be allowed to be mixed in.
[0089] Carbon black is more preferably used because a desired hole region is easily formed inside the carrier. A carrier produced by a method described in Japanese Unexamined Patent Publication No. 2010-208887 or International Publication No. 2009 / 75264 is particularly preferably used.
[0090] In addition to the above-mentioned carbon materials, porous metals such as Sn (tin) and Ti (titanium), and further conductive metal oxides may be used as the carrier.
[0091] The BET specific surface area of the carrier may be sufficient to support the catalyst component in a highly dispersed manner. The BET specific surface area of the carrier is substantially the same as the BET specific surface area of the catalyst. The BET specific surface area of the carrier is preferably 1000 to 3000 m 2 / g, more preferably 1100 to 1800 m 2 / g. If it is the specific surface area as described above, sufficient fine pores and micropores can be ensured, so it is possible to ensure sufficient micropores (lower gas transport resistance) for gas transport, and more metal catalysts can be stored (loaded) by the fine pores. In addition, the electrolyte and the metal catalyst of the catalyst layer are physically separated (the contact between the metal catalyst and the electrolyte can be more effectively suppressed and prevented). Therefore, the activity of the metal catalyst can be more effectively utilized. In addition, by utilizing the presence of many micropores and fine pores, the role and effect of the present invention can be more significantly exerted, and the catalytic reaction can be more effectively promoted. In addition, the balance between the dispersibility of the catalyst component on the catalyst carrier and the effective utilization rate of the catalyst component can be appropriately controlled. In addition, the micropores act as a gas transport path, and the three-phase interface is more significantly formed by water, which can further improve the catalytic activity.
[0092] The average particle size of the carrier is preferably 20 to 100 nm. If it is in this range, even if the above-mentioned hole structure is provided on the carrier, the mechanical strength can be maintained, and the thickness of the catalyst layer can be controlled within an appropriate range. As the value of the "average particle size of the carrier", unless otherwise specified, the value calculated as the average value of the particle size of the particles observed in several to dozens of fields of view using an observation device such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM) is adopted. In addition, "particle size" refers to the maximum distance between any two points on the contour line of the particle.
[0093] In the present invention, as long as the carrier has the above-mentioned micropores and the pore distribution of fine pores in the catalyst, it is not necessary to use the above-mentioned granular porous carrier.
[0094] That is, as carriers, non-porous conductive carriers or non-woven fabrics made of carbon fibers, carbon paper, carbon cloth, etc. constituting the gas diffusion layer are also mentioned. In this case, the catalyst can be supported on these non-porous conductive carriers, or directly attached to non-woven fabrics made of carbon fibers, carbon paper, carbon cloth, etc. constituting the gas diffusion layer of the membrane electrode assembly.
[0095] The metal catalyst that can be used in the present invention has the function of exerting a catalytic effect on an electrochemical reaction. The metal catalyst used in the anode catalyst layer is not particularly limited as long as it has a catalytic effect on the oxidation reaction of hydrogen, and a known catalyst can also be used. In addition, the metal catalyst used in the cathode catalyst layer is also not particularly limited as long as it has a catalytic effect on the reduction reaction of oxygen, and a known catalyst can also be used. Specifically, it can be selected from metals such as platinum, ruthenium, iridium, rhodium, palladium, osmium, tungsten, lead, iron, copper, silver, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, and their alloys.
[0096] Among them, in order to improve the catalytic activity, the resistance to poisoning of carbon monoxide, etc., the heat resistance, etc., it is preferred to use a catalyst containing at least platinum. That is, the metal catalyst is preferably platinum, or preferably contains platinum and metal components other than platinum, more preferably platinum or a platinum-containing alloy. Such a metal catalyst can exert high activity. The composition of the above alloy also depends on the type of metal to be alloyed, but the content of platinum can be set to 30 to 90 atomic%, and the content of the metal alloyed with platinum can be set to 10 to 70 atomic%. In addition, alloys are usually alloys in which one or more metal elements or non-metallic elements are added to metal elements, and are a general term for alloys with metallic properties. In the structure of the alloy, there are eutectic alloys in which the component elements become separate crystals, which can be said to be a mixture, substances in which the component elements are completely dissolved into a solid solution, substances in which the component elements form intermetallic compounds or metal and non-metal compounds, etc., in this application, any substance can be used. At this time, the metal catalyst used in the anode catalyst layer and the metal catalyst used in the cathode catalyst layer can be appropriately selected from the above. In this specification, unless otherwise specified, the description of the metal catalyst for the anode catalyst layer and the cathode catalyst layer is the same definition for both. However, the metal catalysts of the anode catalyst layer and the cathode catalyst layer do not need to be the same, and can be appropriately selected so as to exert the desired effects as described above.
[0097] The shape or size of the metal catalyst (catalyst component) is not particularly limited, and the same shape and size as the known catalyst component can be used. As a shape, for example, granular, flaky, layered, etc. can be used, but preferably granular. At this time, the average particle size of the metal catalyst (metal catalyst particles) is not particularly limited, but preferably more than 3nm, more preferably more than 3nm and less than 30nm, and particularly preferably more than 3nm and less than 10nm. If the average particle size of the metal catalyst is more than 3nm, the metal catalyst is relatively firmly supported in the fine pores, and more effectively inhibits and prevents contact with the electrolyte in the catalyst layer. In addition, the micropores are not blocked by the metal catalyst, and the gas transport path can be better ensured, and the gas transport resistance can be further reduced. In addition, dissolution caused by potential changes can also be prevented, and the performance degradation of time-effectiveness can be suppressed. Therefore, the catalytic activity can be further improved, that is, the catalytic reaction can be more effectively promoted. On the other hand, if the average particle size of the metal catalyst particles is less than 30nm, the metal catalyst can be supported on the fine pores of the carrier by a simple method, and the electrolyte coverage of the metal catalyst can be reduced. In addition, the "average particle size of the metal catalyst particles" of the present invention can be measured as a crystallite diameter calculated from the half-value width of the diffraction peak of the metal catalyst component by X-ray diffraction, or as an average value of the particle size of the metal catalyst particles investigated by a transmission electron microscope (TEM).
[0098] In this method, the catalyst content per unit catalyst coating area (mg / cm 2 ) is not particularly limited as long as sufficient catalyst dispersion on the carrier and power generation performance can be obtained, for example, 0.01 to 1 mg / cm 2 When the catalyst contains platinum or a platinum-containing alloy, the platinum content per unit catalyst coating area is preferably 0.5 mg / cm 2 The use of expensive precious metal catalysts such as platinum (Pt) or platinum alloys is the main reason for the high price of fuel cells. Therefore, it is preferred to reduce the amount of expensive platinum used (platinum content) to the above range to reduce costs. The lower limit is not particularly limited as long as the power generation performance can be obtained, for example, 0.01 mg / cm 2 More preferably, the platinum content is 0.02 to 0.4 mg / cm 2 In this method, the activity per catalyst weight can be increased by controlling the pore structure of the carrier, so that the amount of expensive catalyst used can be reduced.
[0099] In addition, in this specification, the content of catalyst (platinum) per unit catalyst coating area (mg / cm 2 )” was measured (confirmed) using inductively coupled plasma emission spectroscopy (ICP). The desired “catalyst (platinum) content per unit catalyst coating area (mg / cm 2 The method of ")" can also be easily performed by those skilled in the art, and the amount can be adjusted by controlling the composition of the slurry (catalyst concentration) and the coating amount.
[0100] In addition, the amount of catalyst on the carrier (sometimes also referred to as the loading rate) can be preferably set to 10 to 80% by weight, and more preferably set to 20 to 70% by weight relative to the total amount of the catalyst carrier (i.e., the carrier and the catalyst). If the loading is within the above range, sufficient dispersion of the catalyst component on the carrier, improvement of power generation performance, economic advantages, and catalytic activity per unit weight can be achieved, so it is preferred.
[0101] [Catalyst layer]
[0102] As described above, the catalyst of the present invention can reduce gas transport resistance and can exert high catalytic activity, that is, can promote catalytic reaction. Therefore, the catalyst of the present invention can be preferably used in an electrode catalyst layer for a fuel cell. That is, the present invention also provides an electrode catalyst layer for a fuel cell containing the catalyst of the present invention and the electrode catalyst.
[0103] Figure 3 Schematic diagram showing the relationship between the catalyst and the electrolyte in the catalyst layer according to one embodiment of the present invention. Figure 3As shown, in the catalyst layer of the present invention, the catalyst is covered by the electrolyte 26, but the electrolyte 26 does not penetrate into the fine pores 24 (and further the micropores 25) of the catalyst (carrier 23). Therefore, the metal catalyst 22 on the surface of the carrier 23 is in contact with the electrolyte 26, but the metal catalyst 22 supported inside the fine pores 24 is in a non-contact state with the electrolyte 26. The metal catalyst in the fine pores forms a three-phase interface of oxygen and water in a non-contact state with the electrolyte, thereby ensuring the reaction active area of the metal catalyst.
[0104] The catalyst of the present invention may also be present in either the cathode catalyst layer or the anode catalyst layer, but is preferably used in the cathode catalyst layer. This is because, as described above, the catalyst of the present invention forms a three-phase interface with water even when not in contact with the electrolyte, and the catalyst can be effectively utilized, but water is formed in the cathode catalyst layer.
[0105] The electrolyte is not particularly limited, but is preferably an ion-conducting polymer electrolyte. The polymer electrolyte is also called a proton-conducting polymer because it plays a role in transferring protons generated around the catalytic active material on the fuel electrode side.
[0106] The polymer electrolyte is not particularly limited, and conventionally known knowledge may be appropriately referred to. Polymer electrolytes are roughly classified into fluorine-based polymer electrolytes and hydrocarbon-based polymer electrolytes, depending on the type of ion exchange resin as a constituent material.
[0107] As the ion exchange resin constituting the fluorine-based polymer electrolyte, for example, perfluorosulfonic acid resin (registered trademark, manufactured by Dupont Co., Ltd.), perfluorocarboxylic acid resin (registered trademark, manufactured by Asahi Kasei Co., Ltd.), perfluorocarbonic acid resin (registered trademark, manufactured by Asahi Glass Co., Ltd.), etc., perfluorocarbon phosphonic acid polymers, trifluorostyrene sulfonic acid polymers, ethylene tetrafluoroethylene-g-styrene sulfonic acid polymers, ethylene-tetrafluoroethylene copolymers, polyvinylidene fluoride-perfluorocarbon sulfonic acid polymers, etc. From the viewpoint of excellent heat resistance, chemical stability, durability, and mechanical strength, it is preferred to use these fluorine-based polymer electrolytes, and it is particularly preferred to use a fluorine-based polymer electrolyte composed of a perfluorocarbon sulfonic acid polymer.
[0108] As hydrocarbon electrolytes, specifically, sulfonated polyethersulfone (S-PES), sulfonated polyaryletherketone, sulfonated poly-p-benzimidazolyl, phosphinated polybenzimidazolyl, sulfonated poly-p-phenylene, sulfonated polyetheretherketone (S-PEEK), sulfonated poly-p-phenylene (S-PPP), etc. can be cited. From the manufacturing point of view that the raw materials are cheap, the manufacturing process is simple, and the selectivity of the materials is high, it is preferred to use these hydrocarbon polymer electrolytes. In addition, the above-mentioned ion exchange resins can be used alone or in combination of two or more. In addition, it is not limited to the above-mentioned materials, and other materials can also be used.
[0109] In the polymer electrolyte responsible for proton transfer, the conductivity of the proton is important. Here, when the EW of the polymer electrolyte is too large, the ion conductivity of the catalyst layer as a whole decreases. Therefore, the catalyst layer of this mode preferably contains a polymer electrolyte with a small EW. Specifically, the catalyst layer of this mode preferably contains a polymer electrolyte with an EW of 1500g / eq. or less, more preferably contains a polymer electrolyte with an EW of 1200g / eq. or less, and particularly preferably contains a polymer electrolyte with an EW of 1000g / eq. or less.
[0110] On the other hand, when EW is too small, the hydrophilicity is too high, and the smooth movement of water is difficult. From this point of view, the EW of the polymer electrolyte is preferably 600g / eq. or more. In addition, EW (Equivalent Weight) represents the equivalent weight of the exchange group with proton conductivity. The equivalent weight is the dry weight of the ion exchange membrane per 1 equivalent of ion exchange group, and is expressed in "g / eq" units.
[0111] In addition, the catalyst layer contains two or more polymer electrolytes with different EW in the power generation surface. In this case, the polymer electrolyte with the lowest EW is preferably used in the area where the relative humidity of the gas in the flow path is 90% or less. By adopting this material configuration, the resistance value becomes smaller regardless of whether it is a current density area or not, and the battery performance can be improved. As a polymer electrolyte used in the area where the relative humidity of the gas in the flow path is 90% or less, that is, the EW of the polymer electrolyte with the lowest EW is preferably 900g / eq. or less. As a result, the above-mentioned effect is more reliable and significant.
[0112] Furthermore, it is best to use the polymer electrolyte with the lowest EW in the area where the temperature is higher than the average temperature of the cooling water inlet and outlet. This will reduce the resistance value regardless of the current density area, and further improve the battery performance.
[0113] Furthermore, from the perspective of reducing the resistance value of the fuel cell system, the polymer electrolyte with the lowest EW is preferably used in a region within 3 / 5 of the flow path length from the gas supply port of at least one of the fuel gas and the oxidant gas.
[0114] The catalyst layer of this method may also contain a liquid proton conductive material between the catalyst and the polymer electrolyte that can connect the catalyst and the polymer electrolyte into a proton-conducting state. By introducing the liquid proton conductive material, a proton transport path through the liquid proton conductive material can be ensured between the catalyst and the polymer electrolyte, and the protons required for power generation can be efficiently transported to the catalyst surface. As a result, the utilization efficiency of the catalyst is improved, so the amount of catalyst used can be reduced while maintaining power generation performance. The liquid proton conductive material only needs to be sandwiched between the catalyst and the polymer electrolyte, and can be arranged in the holes (secondary holes) between the porous carriers in the catalyst layer or in the holes (micropores or fine holes: primary holes) in the porous carriers.
[0115] The liquid proton conductive material is not particularly limited as long as it has ion conductivity and functions to form a proton transport path between the catalyst and the polymer electrolyte. Specifically, it includes: water, protic ionic liquids, perchloric acid aqueous solution, nitric acid aqueous solution, formic acid aqueous solution, acetic acid aqueous solution, etc.
[0116] When water is used as the liquid proton conductive material, water as the liquid proton conductive material can be introduced into the catalyst layer by wetting the catalyst layer with a small amount of liquid water or humidified gas before starting power generation. In addition, the generated water produced by the electrochemical reaction when the fuel cell is working can also be used as the liquid proton conductive material. Therefore, it is not necessary to maintain the liquid proton conductive material when the fuel cell starts operating. For example, it is best to set the surface distance between the catalyst and the electrolyte to be greater than the diameter of the oxygen ions that constitute the water molecules, that is, 0.28nm. By maintaining this distance, it is possible to maintain the non-contact state of the catalyst and the polymer electrolyte while allowing water (liquid proton conductive material) to intervene between the catalyst and the polymer electrolyte (liquid conductive material retaining portion), thereby ensuring the proton transport path achieved by the water between the two.
[0117] When using a liquid other than water such as an ionic liquid as a liquid proton conductive material, it is best to disperse the ionic liquid, polymer electrolyte and catalyst in a solution when preparing the catalyst ink, but the ionic liquid can also be added when the catalyst is coated on the catalyst layer substrate.
[0118] In the catalyst of the present invention, the total area of the catalyst in contact with the polymer electrolyte is smaller than the total area of the catalyst exposed in the liquid conductive material retaining portion.
[0119] The comparison of these two areas can be performed, for example, by finding the relationship between the capacities of the double electric layer formed at the catalyst-polymer electrolyte interface and the catalyst-liquid proton conductive material interface when the liquid conductive material retaining portion is filled with the liquid proton conductive material. That is, the double electric layer capacity is proportional to the area of the electrochemically effective interface, so if the double electric layer capacity formed at the catalyst-electrolyte interface is smaller than the double electric layer capacity formed at the catalyst-liquid proton conductive material interface, the contact area of the catalyst with the electrolyte is smaller than the exposed area to the liquid conductive material retaining portion.
[0120] Here, the measurement method of the double layer capacity formed at the catalyst-electrolyte interface and the catalyst-liquid proton conductive material interface is explained. In other words, the relationship between the size of the contact area between the catalyst-electrolyte and the catalyst-liquid proton conductive material (the method for determining the relationship between the contact area of the catalyst with the electrolyte and the exposure area to the liquid conductive material retaining portion) is explained.
[0121] That is, in the catalyst layer of this embodiment,
[0122] (1) Catalyst-Polyelectrolyte (C-S)
[0123] (2) Catalyst-liquid proton conducting material (C-L)
[0124] (3) Porous carrier - polymer electrolyte (Cr-S)
[0125] (4) Porous carrier-liquid proton conducting material (Cr-L)
[0126] The above four interfaces can contribute to the double layer capacity (Cdl).
[0127] As mentioned above, since the double layer capacity is proportional to the electrochemically effective interface area, we only need to calculate Cdl C-S (Double layer capacity at the catalyst-polymer electrolyte interface) and Cdl C-L (Catalyst-liquid proton conductive material interface double layer capacity) is sufficient. Furthermore, the contribution of the above four interfaces to the double layer capacity (Cdl) can be separated as follows.
[0128] First, for example, the double layer capacity is measured under high humidification conditions such as 100% RH and low humidification conditions such as 10% RH or less. In addition, as a method for measuring the double layer capacity, cyclic voltammetry or electrochemical impedance spectroscopy can be cited. From the comparison of the two, the contribution of the liquid proton conductive material (in this case, "water") can be separated, that is, the above (2) and (4) can be separated.
[0129] By further deactivating the catalyst, for example, when Pt is used as a catalyst, CO gas is supplied to the electrode to be measured, and the catalyst is deactivated by adsorption of CO on the Pt surface, and the contribution to the double-layer capacity can be separated. In this state, as described above, the double-layer capacity under high humidification and low humidification conditions is measured in the same way, and the contribution of the catalyst can be separated from the comparison between the two, that is, the above (1) and (2) can be separated.
[0130] By doing so, it is possible to separate the contributions of all of (1) to (4) above, and to determine the electric double layer capacity formed at both interfaces between the catalyst and the polymer electrolyte and the liquid proton conductive material.
[0131] That is, the measured value (A) under the high humidification state is the double electric layer capacity formed on the entire interface of (1) to (4) above, and the measured value (B) under the low humidification state is the double electric layer capacity formed on the interface of (1) and (3) above. In addition, the measured value (C) under the catalyst deactivation and high humidification state is the double electric layer capacity formed on the interface of (3) and (4) above, and the measured value (D) under the catalyst deactivation and low humidification state is the double electric layer capacity formed on the interface of (3) above.
[0132] Therefore, the difference between A and C is the double layer capacity formed at the interface of (1) and (2), and the difference between B and D is the double layer capacity formed at the interface of (1). Furthermore, if the difference between these values, (A-C)-(B-D), is calculated, the double layer capacity formed at the interface of (2) can be obtained. In addition, in addition to the above method, the contact area of the catalyst with the polymer electrolyte or the exposed area to the conductive material holding portion can also be obtained by, for example, TEM (transmission electron microscope) tomography.
[0133] If necessary, the catalyst layer may contain additives such as water-repellents such as polytetrafluoroethylene, polyhexafluoropropylene, and tetrafluoroethylene-hexafluoropropylene copolymers, dispersants such as surfactants, thickeners such as glycerin, ethylene glycol (EG), polyvinyl alcohol (PVA), and propylene glycol (PG), and pore-forming agents.
[0134] The thickness (dry film thickness) of the catalyst layer is preferably 0.05 to 30 μm, more preferably 1 to 20 μm, and further preferably 2 to 15 μm. In addition, the above thickness applies to both the cathode catalyst layer and the anode catalyst layer. However, the thickness of the cathode catalyst layer and the anode catalyst layer may be the same or different.
[0135] (Method for producing catalyst layer)
[0136] The following describes a preferred embodiment for producing the catalyst layer, but the technical scope of the present invention is not limited to the following embodiment. In addition, the conditions such as the material of each component of the catalyst layer are as described above, so the description is omitted here.
[0137] First, a carrier (also referred to as a "porous carrier" or "conductive porous carrier" in this specification) is prepared. Specifically, it can be prepared as described in the above-mentioned carrier manufacturing method. Thus, holes with a specific hole distribution (having micropores and fine pores, and the hole volume of the micropores is 0.3cc / g carrier or more and / or the model radius of the hole distribution of the micropores is 0.3nm or more and less than 1nm) can be formed in the carrier.
[0138] Next, the catalyst is loaded on a porous carrier to prepare a catalyst powder. The loading of the catalyst on the porous carrier can be carried out by a known method. For example, known methods such as impregnation method, liquid phase reduction loading method, evaporation drying method, colloidal adsorption method, spray pyrolysis method, reverse micelle (microemulsion method) can be used. In addition, in order to make the average particle size of the metal catalyst into the desired range, it is also possible to heat treat the metal catalyst in a reducing environment after loading it on the carrier. At this time, the heating treatment temperature is preferably in the range of 300 to 1200°C, more preferably in the range of 500 to 1150°C, and particularly preferably in the range of 700 to 1000°C. In addition, the reducing environment is not particularly limited as long as it helps the particle growth of the metal catalyst, but it is preferably carried out in a mixed environment of a reducing gas and an inert gas. The reducing gas is not particularly limited, but preferably hydrogen (H2) gas. In addition, the inert gas is not particularly limited, but helium (He), neon (Ne), argon (Ar), krypton (Kr), xenon (Xe), and nitrogen (N2) can be used. The above-mentioned inert gas may be used alone or in the form of a mixed gas of two or more. In addition, the heating treatment time is preferably 0.1 to 2 hours, more preferably 0.5 to 1.5 hours.
[0139] Next, a catalyst ink containing catalyst powder, a polymer electrolyte, and a solvent is prepared. There is no particular limitation on the solvent, and the usual solvent used to form the catalyst layer can also be used. Specifically, water such as tap water, purified water, ion exchange water, and distilled water, cyclohexanol, methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, isobutanol, and tert-butanol, lower alcohols having 1 to 4 carbon atoms, propylene glycol, benzene, toluene, and xylene can be cited. In addition to these, butyl acetate, dimethyl ether, ethylene glycol, and the like can also be used as solvents. These solvents can be used alone or in the form of a mixed solution of two or more.
[0140] The amount of solvent constituting the catalyst ink is not particularly limited as long as it is an amount that can completely dissolve the electrolyte. Specifically, the concentration of the solid content of the catalyst powder and the polymer electrolyte in the electrode catalyst ink is preferably set to 1 to 50% by weight, and more preferably to 5 to 30% by weight.
[0141] In addition, when using additives such as waterproofing agents, dispersants, thickeners, pore-forming agents, etc., these additives can be added to the catalyst ink. In this case, the amount of the additives added is not particularly limited as long as it does not hinder the above-mentioned effects of the present invention. For example, the amount of the additives added is preferably 5 to 20% by weight relative to the total weight of the electrode catalyst ink.
[0142] Next, the catalyst ink is applied to the surface of the substrate. The method for applying the catalyst ink to the substrate is not particularly limited, and a known method can be used. Specifically, a known method such as a spray (spray coating) method, an oil printing method, a mold coating method, a screen printing method, and a scraper coating method can be used.
[0143] At this time, as a substrate for coating the catalyst ink, a solid polymer electrolyte membrane (electrolyte layer) or a gas diffusion substrate (gas diffusion layer) can be used. In this case, after a catalyst layer is formed on the surface of the solid polymer electrolyte membrane (electrolyte layer) or the gas diffusion substrate (gas diffusion layer), the obtained laminate can be directly used for the manufacture of the membrane electrode assembly. Alternatively, a peelable substrate such as a polytetrafluoroethylene (PTFE) [Teflon (Teflon) (registered trademark)] sheet can be used as a substrate, and after a catalyst layer is formed on the substrate, the catalyst layer is partially peeled off from the substrate to obtain a catalyst layer.
[0144] Finally, the applied layer (film) of the catalyst ink is dried in an air environment or an inert gas environment at room temperature to 150° C. for 1 to 60 minutes. Thus, a catalyst layer is formed.
[0145] (Membrane Electrode Assembly)
[0146] According to a further embodiment of the present invention, a fuel cell membrane electrode assembly containing the above-mentioned fuel cell electrode catalyst layer is provided. That is, a fuel cell membrane electrode assembly having a solid polymer electrolyte membrane 2, a cathode catalyst layer arranged on one side of the above-mentioned electrolyte membrane, an anode catalyst layer arranged on the other side of the above-mentioned electrolyte membrane, and a pair of gas diffusion layers (4a, 4c) sandwiching the above-mentioned electrolyte membrane 2 and the above-mentioned anode catalyst layer 3a and the above-mentioned cathode catalyst layer 3c is provided. Moreover, in the membrane electrode assembly, at least one of the above-mentioned cathode catalyst layer and the anode catalyst layer is a catalyst layer of the above-mentioned embodiment.
[0147] Among them, when considering the necessity of improving proton conductivity and the transport characteristics (gas diffusion) of the reaction gas (especially O2), at least the cathode catalyst layer is preferably the catalyst layer of the above-mentioned embodiment. Among them, the catalyst layer of the above-mentioned form can be used as an anode catalyst layer, or as both a cathode catalyst layer and an anode catalyst layer, etc., without special restrictions.
[0148] According to a further embodiment of the present invention, there is provided a fuel cell having the membrane electrode assembly of the above embodiment. That is, one embodiment of the present invention is a fuel cell having a pair of anode separators and cathode separators sandwiching the membrane electrode assembly of the above embodiment.
[0149] Below, refer to Figure 1 The components of the PEFC 1 using the catalyst layer of the above embodiment will be described. The present invention is characterized in the catalyst layer. Therefore, the specific aspects of the components other than the catalyst layer constituting the fuel cell can be appropriately modified with reference to the prior art.
[0150] (Electrolyte membrane)
[0151] like Figure 1 As shown in the embodiment shown, the electrolyte membrane is composed of, for example, a solid polymer electrolyte membrane 2. The solid polymer electrolyte membrane 2 has a function of selectively transmitting protons generated by the anode catalyst layer 3a to the cathode catalyst layer 3c along the membrane thickness direction when the PEFC 1 is in operation. In addition, the solid polymer electrolyte membrane 2 also has a function as a partition wall for preventing the fuel gas supplied to the anode side and the oxidant gas supplied to the cathode side from mixing.
[0152] As the electrolyte material constituting the solid polymer electrolyte membrane 2, there is no particular limitation, and existing known cognition can be appropriately referred to. For example, the fluorine-based polymer electrolyte or hydrocarbon-based polymer electrolyte described above as a polymer electrolyte can be used. At this time, it is not necessary to use the same polymer electrolyte as the polymer electrolyte used in the catalyst layer.
[0153] The thickness of the electrolyte layer can be appropriately determined in consideration of the characteristics of the obtained fuel cell, and there is no particular limitation. The thickness of the electrolyte layer is generally about 5 to 300 μm. When the thickness of the electrolyte layer is within this range, the strength during film formation or the balance between durability during use and output characteristics during use can be appropriately controlled.
[0154] (Gas Diffusion Layer)
[0155] The gas diffusion layer (anode gas diffusion layer 4a, cathode gas diffusion layer 4c) has the function of promoting diffusion of gas (fuel gas or oxidant gas) supplied to the catalyst layer (3a, 3c) through the gas flow path (6a, 6c) of the separator, and the function of serving as an electron conduction path.
[0156] The material of the substrate constituting the gas diffusion layer (4a, 4c) is not particularly limited, and reference may be made to existing known knowledge as appropriate. For example, sheet materials having conductivity and porosity such as carbon fabrics, paper-like papermaking bodies, felts, and non-woven fabrics may be cited. The thickness of the substrate may be appropriately determined in consideration of the characteristics of the obtained gas diffusion layer, and may be set to about 30 to 500 μm. If the thickness of the substrate is within this range, the balance between mechanical strength and the diffusibility of gas, water, etc. may be appropriately controlled.
[0157] The gas diffusion layer preferably contains a water-repellent in order to further improve water resistance and prevent water infiltration, etc. The water-repellent is not particularly limited, but examples thereof include fluorine-based polymer materials such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), polyhexafluoropropylene, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), polypropylene, polyethylene, etc.
[0158] In order to further improve water repellency, the gas diffusion layer may include a carbon particle layer (microporous layer; MPL, not shown) composed of aggregates of carbon particles containing a water repellent on the catalyst layer side of the substrate.
[0159] The carbon particles contained in the carbon particle layer are not particularly limited, and existing known materials such as carbon black, graphite, and expanded graphite can be appropriately used. Among them, because of excellent electronic conductivity and large specific surface area, it is preferred to use carbon black such as oil furnace carbon black, channel carbon black, lampblack carbon black, thermal cracking carbon black, and acetylene black. The average particle size of the carbon particles can be set to about 10 to 100 nm. As a result, high drainage can be achieved by capillary force, and the contact with the catalyst layer can also be improved.
[0160] Examples of the water repellent used for the carbon particle layer include the same water repellents as those mentioned above, but among these, fluorine-based polymer materials are preferably used because of their excellent water repellency, corrosion resistance during electrode reaction, and the like.
[0161] Considering the balance between water repellency and electron conductivity, the mixing ratio of the carbon particles and the water repellent in the carbon particle layer can be set to about 90:10 to 40:60 (carbon particles: water repellent) by weight. In addition, the thickness of the carbon particle layer is not particularly limited and can be appropriately determined in consideration of the water repellency of the resulting gas diffusion layer.
[0162] (Method for producing membrane electrode assembly)
[0163] There are no particular restrictions on the method for making the membrane electrode assembly, and existing known methods can be used. For example, a method of joining a gas diffusion layer to a layer formed by transferring or coating a catalyst layer on a solid polymer electrolyte membrane using a hot press and drying it, or a method of making two gas diffusion electrodes (GDEs) by pre-coating a catalyst layer on the microporous layer side of the gas diffusion layer (one side of the substrate layer in the case of no microporous layer) and drying it, and then joining the gas diffusion electrode to both sides of the solid polymer electrolyte membrane using a hot press. The coating and bonding conditions of the hot press, etc. can be appropriately adjusted according to the type of polymer electrolyte (perfluorosulfonic acid system or hydrocarbon system) in the solid polymer electrolyte membrane or catalyst layer.
[0164] (Partition)
[0165] When a plurality of single cells of a fuel cell such as a solid polymer fuel cell are connected in series to form a fuel cell group, the separator has the function of electrically connecting each single cell in series. In addition, the separator also has the function of being a partition wall that separates the fuel gas, the oxidant gas, and the coolant from each other. In order to ensure these flow paths, as described above, it is preferred to respectively set a gas flow path and a cooling flow path on the separator. As the material constituting the separator, existing known materials such as carbon such as dense carbon graphite, carbon plate, or metals such as stainless steel can be appropriately used without restriction. The thickness or size of the separator, the shape or size of each flow path to be set, etc. are not particularly limited, and can be appropriately determined considering the desired output characteristics of the obtained fuel cell.
[0166] The method for producing the fuel cell is not particularly limited, and conventional knowledge in the field of fuel cells may be appropriately referred to.
[0167] Furthermore, a fuel cell stack may be formed in which a plurality of membrane electrode assemblies are stacked and connected in series via a separator so that the fuel cell can exert a desired voltage. The shape of the fuel cell is not particularly limited, and may be appropriately determined so as to obtain the desired battery characteristics such as voltage.
[0168] The above-mentioned PEFC or membrane electrode assembly uses a catalyst layer having excellent power generation performance and durability. Therefore, the PEFC or membrane electrode assembly is excellent in power generation performance and durability.
[0169] The PEFC of the present embodiment and a fuel cell stack using the PEFC can be mounted on a vehicle as a driving power source, for example.
[0170] Example
[0171] The effects of the present invention are described using the following examples and comparative examples, but the technical scope of the present invention is not limited to the following examples.
[0172] Synthesis example 1
[0173] The following method was used to prepare a micropore having a pore volume of 0.92 cc / g, a fine pore having a pore volume of 1.53 cc / g, a micropore model diameter of 0.8 nm, a fine pore model diameter of 2.4 nm, and a BET specific surface area of 1600 m 2 / g of carrier A. Specifically, carrier A was prepared by the method described in Japanese Patent Application Laid-Open No. 2010-208887 and the like.
[0174] Synthesis example 2
[0175] The following method was used to prepare a micropore having a pore volume of 1.01 cc / g, a fine pore having a pore volume of 1.49 cc / g, a micropore model diameter of 0.8 nm, a fine pore model diameter of 2.4 nm, and a BET specific surface area of 1600 m 2 / g of carrier B. Specifically, after carrier A is prepared, carrier B is produced by pulverizing the carrier A using a bead mill.
[0176] Synthesis example 3
[0177] The following method was used to prepare a nanoporous material having a pore volume of 1.04 cc / g, a fine pore volume of 0.92 cc / g, a micropore model diameter of 0.65 nm, a fine pore model diameter of 1.2 nm, and a BET specific surface area of 1770 m 2 / g of carrier C. Specifically, carrier C is prepared by the method described in International Publication No. 2009 / 75264 and the like.
[0178] Example 1
[0179] Using the carrier A prepared by the above-mentioned Synthesis Example 1, platinum (Pt) having an average particle size of more than 3 nm and less than 5 nm is loaded as a metal catalyst on the carrier A in a manner that the loading rate becomes 30% by weight, to obtain catalyst powder A. That is, 46 g of the carrier A is immersed in 1000 g (platinum content: 46 g) of a dinitrodiamine platinum nitric acid solution having a platinum concentration of 4.6% by mass, and stirred, and then 100 ml of 100% ethanol is added as a reducing agent. The solution is stirred and mixed at boiling point for 7 hours to load platinum on the carrier A. Then, by filtering and drying, a catalyst powder having a loading rate of 30% by weight is obtained. Thereafter, the catalyst powder A is obtained by maintaining it at a temperature of 900° C. for 1 hour under a hydrogen environment.
[0180] The pore volumes of micropores and fine pores, the model diameters of micropores and fine pores, and the BET specific surface area of the catalyst powder A thus obtained were measured. The results are shown in Table 1 below.
[0181] Example 2
[0182] In Example 1, the same operation as in Example 1 was performed except that the carrier B prepared in the above-mentioned Synthesis Example 2 was used instead of the carrier A to obtain a catalyst powder B. The pore volume of micropores and fine pores, the model diameter of micropores and fine pores, and the BET specific surface area of the catalyst powder B thus obtained were measured. The results are shown in Table 1 below.
[0183] Example 3
[0184] In Example 1, the same operation as in Example 1 was performed except that carrier D was used instead of carrier A to obtain catalyst powder C. In addition, carrier D had a micropore void volume of 0.49 cc / g, a fine pore void volume of 0.50 cc / g, a micropore model diameter of 0.45 nm, a fine pore model diameter of 1.7 nm, and a BET specific surface area of 1440 m 2 / g of carrier (manufactured by Capable Co., Ltd., Blackpearls 2000). The pore volumes of micropores and fine pores, model diameters of micropores and fine pores, and BET specific surface area of the catalyst powder C thus obtained were measured. The results are shown in Table 1 below.
[0185] Example 4
[0186] In Example 1, the same operation as in Example 1 was performed except that the carrier C prepared in the above-mentioned Synthesis Example 3 was used instead of the carrier A, thereby obtaining a catalyst powder D. The pore volume of micropores and fine pores, the model diameter of micropores and fine pores, and the BET specific surface area of the catalyst powder D thus obtained were measured. The results are shown in Table 1 below.
[0187] Comparative Example 1
[0188] Using Ketjen Black EC300J (Ketjen Black, international standard) (carrier E), platinum (Pt) with an average particle size of 3 to 5 nm was loaded as a metal catalyst on the carrier E in a manner that the loading rate was 30% by weight, and a comparative catalyst powder F was obtained. That is, 46 g of carrier A was immersed in 1000 g (platinum content: 46 g) of a dinitrodiamine platinum nitric acid solution with a platinum concentration of 4.6% by mass, and stirred, and then 100 ml of 100% ethanol was added as a reducing agent. The solution was stirred and mixed at boiling point for 7 hours to load platinum on the carrier E. Then, by filtering and drying, a comparative catalyst powder E with a loading rate of 50% by weight was obtained. For the comparative catalyst powder E obtained in this way, the hole volume of micropores and fine pores, the model diameter of micropores and fine pores, and the BET specific surface area were measured. The results are shown in Table 1 below. In addition, Table 1 also shows the void volumes of micropores and fine pores of the support before Pt loading and the model diameters of micropores and fine pores.
[0189] in addition, Figure 4 The pore distribution of the comparative catalyst powder E obtained above is shown in FIG. Figure 4 As shown, the model diameters of micropores and fine pores were not clearly observed in the comparative catalyst powder E. Therefore, in the following Table 1, the model diameters of micropores and fine pores of the carrier (before Pt loading) and catalyst (after Pt loading) of the comparative catalyst powder E are indicated by "-".
[0190] Comparative Example 2
[0191] In Comparative Example 1, graphitized Ketjen black (Carrier F) obtained by sintering Carrier E (Ketjen black) at 2000° C. for 1 hour in an electric furnace under a nitrogen environment was used as a carrier instead of Carrier E. The same operation as in Comparative Example 1 was performed to obtain Comparative Catalyst Powder F. For the Comparative Catalyst Powder F obtained in this way, the hole volume of micropores and fine pores, the model diameter of micropores and fine pores, and the BET specific surface area were measured. The results are shown in Table 1 below. In addition, in Table 1, the hole volume of micropores and fine pores of the carrier before Pt loading and the model diameter of micropores and fine pores are also recorded.
[0192] in addition, Figure 4 The pore distribution of the comparative catalyst powder F obtained above is shown in FIG. Figure 4 As shown, the micropores and the model diameter of fine pores were not clearly observed in the comparative catalyst powder F. Therefore, in the following Table 1, the model diameters of micropores and fine pores of the carrier (before Pt loading) and the catalyst (after Pt loading) of the comparative catalyst powder G are indicated by "-".
[0193] Comparative Example 3
[0194] In Comparative Example 1, after platinum was loaded on the carrier, the carrier was kept at 900°C for 1 hour under a hydrogen environment. The same operation as in Comparative Example 1 was performed to obtain a comparative catalyst powder G. The hollow volume of micropores and fine pores, the model diameter of micropores and fine pores, and the BET specific surface area of the comparative catalyst powder G obtained in this way were measured. The results are shown in the following Table 1. In addition, in Table 1, the hollow volume of micropores and fine pores of the carrier before Pt loading and the model diameter of micropores and fine pores are also recorded.
[0195] in addition, Figure 4 The pore distribution of the comparative catalyst powder G obtained above is shown in FIG. Figure 4 As shown, the model diameter of micropores and fine pores was not clearly observed in the comparative catalyst powder H. Therefore, in the following Table 1, the model diameters of micropores and fine pores of the carrier (before Pt loading) and catalyst (after Pt loading) of the comparative catalyst powder G are indicated by "-".
[0196] Example 5
[0197] In Comparative Example 1, except that carrier A was used instead of carrier E, the same operation as in Example 1 was performed to obtain catalyst powder H. The hollow volume of micropores and fine pores, the model diameter of micropores and fine pores, and the BET specific surface area of the catalyst powder H thus obtained were measured. The results are shown in the following Table 1. In addition, in Table 1, the hollow volume of micropores and fine pores of the carrier before Pt loading and the model diameter of micropores and fine pores are also recorded.
[0198] [Table 1]
[0199]
[0200] *1. The unit of hole volume is cc / g carrier.
[0201] *2. The unit of BET specific surface area is m 2 / g carrier
[0202] As can be seen from Table 1, in the catalyst powders A to D and H of the present invention, the hole volumes of both fine pores and micropores are reduced, but the reduction value of the hole volume of fine pores is larger. It is thus observed that in the catalyst of the present invention, the metal catalyst is selectively supported in the holes of fine pores. In addition, in Table 1, in the catalyst powders A to D and H of the present invention, the hole volume of micropores is also reduced slightly, which is presumed to be because the metal catalyst blocks the entrance of the micropores.
[0203] Example 6
[0204] The catalyst powder A prepared in Example 1 and the ionomer dispersion liquid (Nafion (registered trademark) D2020, EW = 1100 g / mol, manufactured by DuPont) as a polymer electrolyte were mixed so that the weight ratio of the carbon support to the ionomer was 0.9. Furthermore, a n-propanol solution (50%) was added as a solvent so that the solid content (Pt + carbon support + ionomer) was 7 wt %, thereby preparing a cathode catalyst ink.
[0205] Using Ketjen black (particle size: 30-60 nm) as a carrier, platinum (Pt) with an average particle size of 2.5 nm was loaded on the carrier as a metal catalyst in a manner that the loading rate was 50% by weight to obtain a catalyst powder. The catalyst powder and an ionomer dispersion liquid (Nafion (registered trademark) D2020, EW=1100 g / mol, manufactured by DuPont) as a polymer electrolyte were mixed in a manner that the weight ratio of the carbon carrier to the ionomer was 0.9. Furthermore, a n-propanol solution (50%) was added as a solvent in a manner that the solid content (Pt+carbon carrier+ionomer) was 7%, and an anode catalyst ink was prepared.
[0206] Next, a sealing gasket (manufactured by Dupont, polynaphthyl ester, thickness: 25 μm (adhesive layer: 10 μm)) was arranged around both sides of the polymer electrolyte membrane (manufactured by Dupont, NAFION NR211, thickness: 25 μm). Next, the catalyst ink was applied to the exposed portion of one side of the polymer electrolyte membrane by spray coating, and the coating was applied to a size of 5 cm × 2 cm. The catalyst ink was dried by keeping the workbench for spray coating at 60°C for 1 minute to obtain an electrode catalyst layer. The platinum loading at this time was 0.15 mg / cm 2 Next, the anode catalyst layer was formed on the electrolyte membrane by spray coating and heat treatment in the same manner as the cathode catalyst layer, thereby obtaining the membrane electrode assembly (1) (MEA (1)) of this example.
[0207] Example 7
[0208] In Example 6, the same operation as in Example 6 was carried out except that the catalyst powder B obtained in Example 2 was used instead of the catalyst powder A, thereby producing a membrane electrode assembly (2) (MEA (2)).
[0209] Example 8
[0210] In Example 6, a membrane electrode assembly (3) (MEA (3)) was produced by the same operation as in Example 6, except that the catalyst powder C obtained in Example 3 was used instead of the catalyst powder A.
[0211] Example 9
[0212] In Example 6, the same operation as in Example 6 was carried out except that the catalyst powder D obtained in Example 4 was used instead of the catalyst powder A, thereby producing a membrane electrode assembly (4) (MEA (4)).
[0213] Comparative Example 4
[0214] In Example 6, the same operation as in Example 6 was carried out except that comparative catalyst powder E obtained in Comparative Example 1 was used instead of catalyst powder A, thereby producing a comparative membrane electrode assembly (1) (comparative MEA (1)).
[0215] Comparative Example 5
[0216] In Example 6, the same operation as in Example 5 was carried out except that comparative catalyst powder F obtained in Comparative Example 2 was used instead of catalyst powder A, thereby producing a comparative membrane electrode assembly (2) (comparative MEA (2)).
[0217] Comparative Example 6
[0218] In Example 6, the same operation as in Example 6 was carried out except that the comparative catalyst powder G obtained in Comparative Example 3 was used instead of the catalyst powder A, thereby producing a comparative membrane electrode assembly (3) (comparative MEA (3)).
[0219] Example 10
[0220] In Example 6, the same operation as in Example 6 was carried out except that the catalyst powder H obtained in Example 5 was used instead of the catalyst powder A, thereby producing a membrane electrode assembly (5) (MEA (5)).
[0221] Experiment 1: Evaluation of oxygen reduction (ORR) activity
[0222] The membrane electrode assemblies (1) to (5) prepared in Examples 6 to 10 and the comparative membrane electrode assemblies (1) to (3) prepared in Comparative Examples 4 to 6 were measured for the generated current (μA / cm2) per unit platinum surface area at 0.9 V under the following evaluation conditions. 2 The results are shown in Table 2 below.
[0223] [Chemistry 2]
[0224] <Evaluation conditions>
[0225] Temperature: 80℃
[0226] Gas composition: Hydrogen (anode side) / oxygen (cathode side)
[0227] Relative humidity: 100%RH / 100%RH
[0228] Pressure: 150kPa(abs) / 150kPa(abs)
[0229] Voltage scanning direction: anode
[0230] Experiment 2: Evaluation of power generation performance
[0231] The membrane electrode assemblies (1) to (5) prepared in Examples 6 to 10 and the comparative membrane electrode assemblies (1) to (3) prepared in Comparative Examples 4 to 6 were measured under the following evaluation conditions at 1.5 A / cm 2 The voltage (V) at 1000 V was used to evaluate the power generation performance. The results are shown in Table 2 below.
[0232] [Chemistry 3]
[0233] <Evaluation conditions>
[0234] Temperature: 80℃
[0235] Gas composition: Hydrogen (anode side) / air (cathode side)
[0236] Relative humidity: 90%RH / 90%RH
[0237] Pressure: 200kPa(abs) / 200kPa(abs)
[0238] Experiment 3: Evaluation of gas transport resistance
[0239] The membrane electrode assemblies (1) to (5) prepared in Examples 6 to 10 and the comparative membrane electrode assemblies (1) to (3) prepared in Comparative Examples 4 to 6 were evaluated for gas transport resistance according to the method described in T. Mashio et al. ECS Trans., 11, 529, (2007). The results are shown in Table 2 below.
[0240] That is, using diluted oxygen, the limiting current density (A / cm 2 At this time, according to the limiting current density (A / cm 2 ) with respect to the oxygen partial pressure (kPa), and the gas transport resistance (s / m) is calculated. The gas transport resistance is proportional to the total pressure of the gas, and can be separated into a component that depends on the total pressure of the gas (the gas transport resistance caused by molecular diffusion) and an independent component. Among them, the former is the transport resistance component of relatively large holes larger than 100nm, such as those present in the gas diffusion layer, and the latter is the transport resistance component of relatively small holes less than 100nm, such as those present in the catalyst layer. In this way, by measuring the total pressure dependence of the gas transport resistance and extracting the components that are independent of the total pressure, the gas transport resistance in the catalyst layer can be obtained.
[0241] [Table 2]
[0242]
[0243] As can be seen from Table 2, the MEAs (1) to (5) using the catalysts of the present invention have significantly lower gas transport resistance and are superior in catalytic activity (oxygen reduction activity) and power generation performance compared to the comparative MEAs (1) to (3) not having the hole distribution specified by the present invention. From the results of Tables 1 and 2, it can be seen that the catalysts of the present invention can exhibit high catalytic activity by improving gas transport properties and forming a three-phase interface with water in the fine pores in a non-contact state with the electrolyte.
[0244] Furthermore, the present application is based on Japanese Patent Application No. 2013-092911 filed on April 25, 2013, the disclosure of which is incorporated herein by reference in its entirety.
Claims
1. A fuel cell electrode catalyst layer, comprising: A catalyst composed of a catalyst carrier and a metal catalyst supported on the catalyst carrier; a polymer electrolyte; and a liquid proton conductive material located between the catalyst and the polymer electrolyte, characterized in that: The catalyst has holes with a radius of less than 1 nm and holes with a radius of more than 1 nm. The hole volume of the hole with a radius less than 1 nm is 1.05 to 2.0 cc / g carrier, The hole volume of the hole with a radius of more than 1 nm is 0.4 to 0.9 cc / g carrier, The metal catalyst comprises: particles supported inside the cavities having a radius of 1 nm or more; particles supported on the outer surface of the catalyst carrier, The number of the metal catalysts supported inside the cavities having a radius of 1 nm or more is greater than the number of the metal catalysts supported on the outer surface of the catalyst carrier.
2. The fuel cell electrode catalyst layer according to claim 1, wherein The model radius of the hole distribution of the holes having a radius of less than 1 nm is 0.3 nm or more and less than 1 nm.
3. The fuel cell electrode catalyst layer according to claim 1 or 2, wherein: The average particle size of the metal catalyst is greater than 3 nm.
4. The fuel cell electrode catalyst layer according to claim 1 or 2, wherein: The model radius of hole distribution of holes having a radius of 1 nm or more in the catalyst is 1 to 5 nm.
5. The fuel cell electrode catalyst layer according to claim 1 or 2, wherein: The BET specific surface area of the catalyst is 1750-1800 m 2 / g carrier or more.
6. The fuel cell electrode catalyst layer according to claim 1 or 2, wherein: The metal catalyst is platinum, or contains platinum and a metal component other than platinum. 7 . A fuel cell membrane electrode assembly comprising the fuel cell electrode catalyst layer according to claim 1 .
8. A fuel cell comprising the membrane electrode assembly for a fuel cell according to claim 7.
Citation Information
Patent Citations
Electrode catalyst for fuel cell with enhanced noble metal utilization efficiency, its manufacturing method, and solid polymer fuel cell equipped with this
JP2007250274A
Porous carbon and method of producing the same
JP2010208887A
Information processing device, information processing method, and program
JP2013092911A
Fuel cell electrode catalyst with improved noble metal utilization efficiency, method for manufacturing the same, and solid polymer fuel cell comprising the same
US20090047559A1
Metal Encapsulated Dendritic Carbon Nanostructure, Carbon Nanostructure, Process for Producing Metal Encapsulated Dendritic Carbon Nanostructure, Process for Producing Carbon Nanostructure, and Capacitor
US20110058308A1